FINANCIAL STATEMENT ANALYSIS OF PT CIPUTRA DEVELOPMENT TBK FOR THE 2020–2024 PERIOD USING RATIO ANALYSIS, COMMON SIZE, TREND, AND DU PONT SYSTEM APPROACHES - Flora Sania; Sapira Br Sembiring; Sarah Obadiyah Ivana; Bunga Citra Lestari; Alya Rahma; Heriyati Chrisna (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the financial capability of PT Ciputra Development Tbk, one of the largest property developers in Indonesia listed on the Indonesia Stock Exchange under the stock code CTRA, over five consecutive years, from 2020 to 2024. The study uses a descriptive quantitative approach by utilizing secondary data in the form of consolidated and audited financial statements published in the company's Annual Report. The analysis techniques used include financial ratio analysis such as liquidity, solvency, profitability, and activity, common size analysis, trend analysis, and the Du Pont System analysis. The results show that the company's current ratio was 177.84 percent in 2020, rose to 242.32 percent in 2023, and then decreased to 198.55 percent in 2024, indicating that the company's liquidity remains in good condition. The ability to pay off debt has continued to improve, as seen from the debt-to-equity ratio dropping from 124.86 percent to 91.03 percent. The company's profitability has shown growth, with Return on Equity rising from 8.62 percent to 9.73 percent, and Return on Assets increasing from 3.36 percent to 4.52 percent. This improvement was driven by revenue growth reaching 38.62 percent during the study period. Common size analysis shows a shift in asset composition more towards current assets and a decrease in liabilities as part of total assets. Overall, PT Ciputra Development Tbk's financial performance from 2020 to 2024 shows a consistent upward trend in various aspects like liquidity, solvency, and profitability.